Exploring recent significant catalytic systems for the conversion of glucose into bio-based chemicals: a concise review - Dharmapriya, Thakshila Nadeeshani; Huang, P.-J. (Elsevier, 2024)
Background: Renewable alternatives for bio-chemical production have gained significant attention. Glucose, as the most abundant monosaccharide globally, has emerged as a pivotal substrate in this pursuit. Consequently, the processes of glucose isomerization into fructose and glucose dehydration into 5-HMF have garnered substantial interest. 5-HMF (5-hydroxymethylfurfural) serves as a platform chemical, enabling the synthesis of valuable biobased compounds, while fructose stands out as a promising precursor for 5-HMF formation. Method: Employing a comprehensive literature review methodology, this paper examines recent advancements in catalytic systems for the conversion of glucose on two primary processes: glucose isomerization into fructose and glucose dehydration into 5-HMF. Significant Findings: This concise review centers on the use of amines as organic base catalysts for glucose isomerization, leading to high selectivity for fructose. It compares the yield and selectivity of fructose achieved with various homogeneous and heterogeneous amine catalysts. Furthermore, it highlights the growing interest in the MIL-101 series of Metal Organic Frameworks (MOFs) for direct glucose dehydration into 5-HMF, comparing the yield and selectivity of 5-HMF attained. This review serves as a guide for future researchers in biomass valorization, offering insights into recent advancements in catalysts for enhanced chemical production efficiency.